Factors Affecting Employee Performance at Perumda Tirta Bumi Serasi Drinking Water, Semarang Regency - Hendri Widiyati Astutiningsih; Agung Guritno (Jurnal Ekonomi dan Bisnis Digital, 2023)
In this study using quantitative methods the data obtained were processed with SPSS. The analysis used in this research includes instrument test, classical assumption test, statistical test and hypothesis test with path analysis. The results of the study show: spiritual intelligence has a significant positive effect on employee performance, burnout and self-control have a negative but not significant effect on employee performance, spiritual intelligence has no significant positive effect on job satisfaction, burnout has an effect negative but not significant on job satisfaction, self-control (locus of control) has a significant positive effect on job satisfaction, job satisfaction has a significant positive effect on employee performance, job satisfaction does not mediate spiritual intelligence and burnout on employee performance, job satisfaction mediates control self (locus of control) on employee performance.